DULCE MARÍA BORRERO: A DIVERSE INTELLECTUAL - Ricardo, Yolanda (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article is a reflection based on information from research undertaken from a socio-historical perspective with analytical, interpretive and critical methodology; it is about the multifaceted personality of the Cuban intellectual Dulce María Borrero. The essential purpose is to provide her intellectual profile in the context and emphasize her contributions to the Republican education of the first half of twentieth century in Cuba, mainly at the primary level, in close interaction with the Cuban socio-educational process of her time.